THU0193 CLINICO-DEMOGRAPHIC, IMMUNOLOGIC AND SYNOVIAL HISTOLOGIC FEATURES INFLUENCING RESPONSE TO JAK-INHIBITORS IN RHEUMATOID ARTHRITIS: A MONOCENTRIC COHORT. (13th June 2020) - Bruno, D.; Gigante, M. R.; Petricca, L.; Fedele, A. L.; Perniola, S.; Gessi, M.; Tolusso, B.; Alivernini, S.; Gremese, E.
Abstract : Background: Janus kinase Inhibitors (JAKis) are approved for the treatment of Rheumatoid Arthritis (RA) in over 40 countries. The updated EULAR recommendations for RA treatment revised the preference of bDMARDs over tsDMARDs based on the new data related to JAKis long-term efficacy and safety. [1]. Objectives: To evaluate the efficacy and safety of JAKis molecules in an observational single center cohort of RA patients in a real life outpatient clinical setting. Methods: 76 RA patients [mean age: 55.7±12.5 years, 64(84.2%) female, disease duration: 120.7±97.2 months, 43 (61.4%) seropositive (AB+) for ACPA and/or IgM-RF, 34(44.7%) with BMI ≥25.0 kg/m2] were followed after starting JAKis treatment monotherapy or in combination with conventional synthetic DMARDs (csDMARDs). At study entry, and every 3 months, the ACR/EULAR core data set variables were recorded for each patient. Clinical improvement and remission rate were evaluated according to Disease Activity Score (DAS) and Clinical Disease Activity Index (CDAI) and any therapy-related adverse effect was reported. Among the whole RA cohort, 20 patients underwent US-guided synovial tissue (ST) biopsy before JAKis treatment and classified using the Krenn score for the semiquantitative assessment of ST inflammation[2]. Results: Among the whole RA cohort who started JAKis [mean follow-up (FU) duration: 6.1±3.7 months], 22(28.9%) showed DAS-defined high disease activity. 54(71.1%) patients were previously treated with at least 1 csDMARD and 33(43.4%) were naive to biologic DMARDs (bDMARDs). Among RA previously exposed to b-DMARDs, 23(30.3%) were using anti-TNF and 14(18.4%) anti-IL6R, whereas 6(7.9%) patients received other bDMARD. In particular, 11(14.5%) patients were previously treated only with one bDMARD. During the FU, 12(15.8%) patients discontinued JAKis [7 due to treatment failure and 5 to adverse events (1 anemia, 2 gastrointestinal intolerance, 2 H.Zoster infection)]. All RA who discontinued JAKis for incomplete or no-response were previously exposed to bDMARDs. DAS Remission was achieved in 29 of 65(44.6%) patients during the FU, of whom 21(32.5%) achieved remission at 3 months. Similarly, 16(24.6%) patients reached CDAI remission of whom 12(18.5%) patients achieved remission at 3 months. At baseline, there were no differences of DAS-remission rate based on age, gender, disease duration, BMI and high disease activity. Similarly, concomitant steroid and csDMARDs therapy did not impact on the rate of DAS and CDAI Remission. However, RA reaching DAS remission during FU had more likely a shorter disease duration (p=0.01) and were less previously exposed to bDMARDs (p=0.001) than patients not achieving DAS remission. Conversely, the DAS Remission rate was higher in AB+ (55.3%) than in AB- RA patients (27.3%, p=0.04). Furthermore, bDMARDs naive RA showed higher probability to reach remission compared to bDMARD previously exposed RA [DAS remission: 66.7% vs 28.9%, respectively, p=0.003; OR(95%): 4.90 (1.69-14.3) and CDAI-remission: 37.0% vs 15.8%, p=0.05; OR(95%CIs): 3.12(0.97-10.10)], regardless to the type of the previous bDMARDs used.Finally, considering the baseline ST features, RA achieving clinical improvement did not differ in terms of Krenn score and microanatomical organization compared to RA not achieving the clinical improvement. Conclusion: The efficacy rate of JAKis therapy is not influenced by BMI and baseline high disease activity. Previous exposure to bDMARDs impacts both on the clinical response and on the rate of JAKis therapy discontinuation. Therapy-related adverse effects mainly occurred in bDMARD previously exposed RA patients. References: [1]Smolen JS, et al. Ann Rheum Dis 2020 [2]Krenn V, et al. Histopathology 2006 Disclosure of Interests: Dario Bruno: None declared, Maria Rita Gigante: None declared, Luca Petricca: None declared, Anna Laura Fedele: None declared, Simone Perniola: None declared, Marco Gessi: None declared, Barbara Tolusso: None declared, Stefano Alivernini: None declared, Elisa Gremese Speakers bureau: Abbvie, BMS, Celgene, Jannsen, Lilly, MSD, Novartis, Pfizer, Sandoz, UCB